AGE–RAGE Stress and Coronary Artery Disease - Prasad, Kailash (International Journal of Angiology, 2021)
Coronary artery atherosclerosis and atherosclerotic plaque rupture cause coronary artery disease (CAD). Advanced glycation end products (AGE) and its cell receptor RAGE, and soluble receptor (sRAGE) and endogenous secretory RAGE (esRAGE) may be involved in the development of atherosclerosis. AGE and its interaction with RAGE are atherogenic, while sRAGE and esRAGE have antiatherogenic effects. AGE–RAGE stress is a ratio of AGE/sRAGE. A high AGE–RAGE stress results in development and progression of CAD and vice-versa. AGE levels in serum and skin, AGE/sRAGE in patients with CAD, and expression of RAGE in animal model of atherosclerosis were higher, while serum levels of esRAGE were lower in patients with CAD compared with controls. Serum levels of sRAGE in CAD patients were contradictory, increased or decreased. This contradictory data may be due to type of patients used, because the sRAGE levels are elevated in diabetics and end-stage renal disease. AGE/sRAGE ratio is elevated in patients with reduced or elevated levels of serum sRAGE. It is to stress that AGE, RAGE, sRAGE, or esRAGE individually cannot serve as universal biomarker. AGE and sRAGE should be measured simultaneously to assess the AGE–RAGE stress. The treatment of CAD should be targeted at reduction in AGE levels, prevention of AGE formation, degradation of AGE in vivo, suppression of RAGE expression, blockade of RAGE, elevation of sRAGE, and use of antioxidants. In conclusion, AGE–RAGE stress would initiate the development and progression of atherosclerosis. Treatment modalities would prevent, regress, and slow the progression of CAD.
Keywords: advanced glycation end products (AGE); cell receptor for AGE; soluble receptors AGE; coronary artery disease (CAD); atherosclerosis; atherosclerotic plaque rupture; AGE–RAGE stress; treatment modalities for AGE-RAGE stress-induced CAD